Analisis kadar logam berat pada limbah industri kelapa sawit berdasarkan hasil pengukuran atomic absorption spectrophotometry (AAS) - Junika Wulandari (Department of Physics – Universitas Negeri Padang UNP, 2016)
Liquid waste of industry palm oil is the most abundant waste produced among other types of waste which is about 60% from 100% processing of fresh fruit bunches. Generally, industrial liquid waste contains heavy metals. Heavy metals are toxic if it exceeds the required levels. To determine levels of heavy metals toThe purpose of research is to test the linearity and sensitivity of heavy metals by AAS method, determine the metal content determine danger. Type of this research is laboratory exsperiment. Samples testing was conducted Baristand Padang. There were two samples group, those are waste palm oil of industry and well water around of waste. Analisys datatechniques which were used linear regression methods and corretation methods. Based on data analysis can be presented three results from research. First, test the linearity and sensitivity test on the validation of methods of analysis of Cu, Cd, Pb and Zn meet the requirements of its use. Second, the levels of Cu, Cd, Pb and Zn in the samples of waste palm oil and water well below the limit of detection of smaller instruments. Finally, the levels of Cu, Cd, Pb and Zn in samples of palm oil waste and water wells are not dangerous because it does not exceed the requirements of Regulation of the Minister of Environment of the Republic of Indonesia Number 5 of 2014 concerning water quality standard of waste and Government Regulation No. 82 of 2001 concerning the management of quality water and water pollution control